Associations Between Religiosity, Perceived Social Support, and Stimulant Use in an Untreated Rural Sample in the U.S.A. (6th June 2016) - Cucciare, Michael A.; Han, Xiaotong; Curran, Geoffrey M.; Booth, Brenda M.
ABSTRACT: Background : Religiosity and perceived social support (SS) may serve as protective factors for more severe substance use in adults. Objectives : This study sought to examine whether aspects of religiosity and SS are associated with longitudinal reductions in stimulant use over three years in an untreated sample of rural drug users. Methods : Respondent-driven sampling was used to recruit stimulant users ( N = 710) from Arkansas, Kentucky, and Ohio. Follow-up interviews were conducted at 6-month intervals for 36 months. Results : Our bivariate findings indicate that higher religiosity was associated with lower odds and fewer days of methamphetamine and cocaine use. After controlling for covariates, higher religiosity was associated with fewer days of crack cocaine use, but more days of methamphetamine use among a small sample of users in the two final interviews. Higher SS from drug-users was also associated with higher odds and days of methamphetamine and powder cocaine use, while higher SS from nondrug users was associated with fewer days of methamphetamine use. Conclusions/Importance : Our bivariate findings suggest that higher levels of religiosity may be helpful for some rural individuals in reducing their drug use over time. However, our multivariate findings suggest a need for further exploration of the potential effects of religiosity on longer-term drug use, especially among those who continue to use methamphetamine and/or remain untreated. Our findings also highlight the potential deleterious effect of SS from drug users on the likelihood and frequency of methamphetamine and powder cocaine use over time among untreated rural drug users.